Redes sociais virtuais de informação sobre amor: comportamento e cultura informacional de usuários do Orkut - Ruleandson do Carmo Cruz (2011)
This research analyses the virtual social networks of information about love formed by the users of the site Orkut, with focus on the behavior and on the informational culture of such users, as well on the social representation of love created by them. As study object, it takes five virtual communities about love existent on the reported site: Se é amor q... seja verdadeiro!, Amor e sexo em debate, Eu ACREDITO no amor, Amor, Respeito e Confiança and O mito do amor romântico. Considers as empirical universe: in general analysis, the topic and enquiry listings that can be found on the cited communities; In specific analysis, five topics of definition of love and 103 profiles from the most active users of the studied communities. It is methodologically structured as a study of multiple incorporated cases. Triangulates the data gotten on the documental analysis of the forums and profiles, as well the answers of the questionnaire applied to the 103 analyzed users, besides interviews with two owners of the communities in evaluation. It builds its theoretical referential by the aid of some of the main theories and theorists from six thematic axis: social network, informational behavior, informational culture, social representation, love and Orkut. Identifies the main social representations of love presented by the users, as liquid love, romantic love, poly love, love as feeling so uncertain that people need to appeal to supernatural powers, love as a practical relation between two individuals, Eros and Psique myth, and love like something that cannot be defined. Delineates the love informational profile of the users, most of them adults, women, involved in relationships, wishful for marriage and that use information about love to personalize their profiles on Orkut. Characterizes the informational behavior as motivated, mainly, by missing feelings for the loved person, extreme happiness, extreme coldness in love, and also as the interest in studding love. Defines the informational culture as something without rules and explicit orientation in most part of the communities. Draws the social networks of information about love and consider them as networks of low density, centrality and intermediation, although there is some of them that can be classified as high density informational networks. Concludes, among other findings, that the social networks in study provide help information and support to the users, and work as hanger-communities.